JURNAL HUKUM ANALISIS YURIDIS PUTUSAN BEBAS DALAM TINDAK PIDANA KORUPSI - Laowo, Yonathan Sebastian (JURNAL EDUCATION AND DEVELOPMENT, 2018)
Juridical analysis against the acquittal in corruption is a normative study in corruption of acquittal given by the judges.The method used is a normative juridical research is through library research is qualitative by using the rule of law so as to outline the problems which exist in accordance with the facts that occurred in the community so that it can be seen what the factors that influence the judge in giving acquittal against perpetrators of corruption. One of the problems that arise in the effort to eradicate corruption is with the acquittal of the perpetrators of corruption. If acquitted continues, it could encourage criminals or others who want to make corruption more daring. This situation will make it difficult for Indonesian nation clean of corruption, collusion and nepotism.     Results from this study showed that there are many external factors that make a judge gave the acquittal and the possibility to the public prosecutor to bring a legal action against the acquittal. This is confirmed by the formulation of the editorial article 244 Criminal Procedure Code, as follows: "Against the decision of the criminal case that was given at the last level by courts other than the Supreme Court, the defendant or the prosecutor may file a request for examination of cassation to the Supreme Court except against the acquittal." in addition to internal factors that exist within the judge or the judiciary. External factors are the authors intent in terms of Act 31 of 1999 jo 20 of 2001 also give a gap with a penalty of a minimum of very low so that interested parties may commit fraud in the case. So the decision of the judge tends to be very low even could lead to acquittal.